Incidence, Prognostic Factors, and Survival Trend in Pineal Gland Tumors: A Population-Based Analysis - Vuong, Huy Gia; Ngo, Tam N. M.; Dunn, Ian F. (Frontiers in Oncology, 2021)
Introduction: Pineal gland tumors are exceedingly rare and account for 0.4-1.0% of brain neoplasms. Their rarity has confounded a clear understanding of the prognostic factors and standards of care for these neoplasms. In this study, we aimed to investigate the incidence, prognostic indicators, and survival trend of tumors emanating from the pineal gland. Methods: We accessed the Surveillance, Epidemiology, End Results (SEER) Program for pineal gland tumors from 1975-2016. A multivariate Cox regression model was used to investigate the impact of clinicopathological parameters on all-cause mortality. For survival trend analysis, we employed the Kaplan Meier curve and pairwise comparisons to examine the trend. Results: We found 1,792 and 310,003 pineal gland and brain neoplasms during 1975-2016 resulting in an incidence of 0.6%. In the multivariate Cox proportional hazards model, older age, male gender, non-germ cell tumor, and receipt of chemotherapy were significantly associated with poor survival (p < 0.001). The extent of resection and radiotherapy administration did not produce survival advantages. Our result also highlighted an increased survival of pineal gland tumors over the years. Conclusion: Our study investigated the prognostic factors that influenced survival in patients with pineal gland tumors. Chemotherapy use adversely affected patient outcomes and should be considered carefully in specific circumstances to avoid its harmful effects. These findings provide important evidence to improve current standards of care for this rare group of tumors. The survival of pineal tumors has improved over time reflecting improvements in current practice.